A mycobacteriophage genomics approach to identify novel mycobacteriophage proteins with mycobactericidal properties. Issue 7 (15th May 2019) - Singh, Shweta; Godavarthi, Sapna; Kumar, Amit; Sen, Ranjan
Abstract : Mycobacteriophages that are specific to mycobacteria are sources of various effector proteins that are capable of eliciting bactericidal responses. We describe a genomics approach in combination with bioinformatics to identify mycobacteriophage proteins that are toxic to mycobacteria upon expression. A genomic library comprising phage genome collections was screened for clones capable of killing Mycobacterium smegmatis strain mc 2 155. We identified four unique clones: clones 45 and 12N (from the mycobacteriophage D29) and clones 66 and 85 (from the mycobacteriophage Che12). The gene products from clones 66 and 45 were identified as Gp49 of the Che12 phage and Gp34 of the D29 phage, respectively. The gene products of the other two clones, 85 and 12N, utilized novel open reading frames (ORFs) coding for synthetic proteins. These four clones (clones 45, 66, 85 and 12N) caused growth defects in M. smegmatis and Mycobacterium bovis upon expression. Clones with Gp49 and Gp34 also induced growth defects in Escherichia coli, indicating that they target conserved host machineries. Their expression induced various morphological changes, indicating that they affected DNA replication and cell division steps. We predicted that Gp34 is a Xis protein that is required in phage DNA excision from the bacterial chromosome. Gp49 is predicted to have an HTH motif with DNA-bending/twisting properties. We suggest that this methodology is useful to identify new phage proteins with the desired properties without laboriously characterizing the individual phages. It is universal and could be applied to other bacteria–phage systems. We speculate that the existence of a virtually unlimited number of phages with unique gene products could offer a cheaper and less hazardous alternative to explore new antimicrobial molecules.